2019
DOI: 10.25273/etj.v7i2.5434
|View full text |Cite
|
Sign up to set email alerts
|

The effect of zimmer twins as digital storytelling on students’ writing narrative text

Abstract: <p class="MsoNormal" style="margin-top: 0cm; margin-right: 5.6pt; margin-bottom: .0001pt; margin-left: 5.8pt; text-align: justify;">The objective of the research to compare of Zimmer twins website tool as digital storytelling than use nondigital in writing text narrative on students writing ability at the eleventh grade of MA  Yayasan Sirojul  Islam Sukolilo 2018/2019 academic year. Zimmer twins media is an animated movie maker based on the website for the students to create their short stories in movies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 2 publications
(2 reference statements)
1
2
0
Order By: Relevance
“…The results of the study from Novita Aryuntini at al (2018) showed the used videoscribe media learning in descriptive writing class can improved students writing skill. It also proved by (Wulandari, et. al: 2019) technology makes faster teaching and learning process.…”
Section: E) Hypothesissupporting
confidence: 62%
“…The results of the study from Novita Aryuntini at al (2018) showed the used videoscribe media learning in descriptive writing class can improved students writing skill. It also proved by (Wulandari, et. al: 2019) technology makes faster teaching and learning process.…”
Section: E) Hypothesissupporting
confidence: 62%
“…Besides that, podcasts convey innovative chances for educators to determine the zones of teaching which are attractive but looks not to be actually tried by teachers (Bartoš, 2008). It is also stated by (Wulandari, Ulfa, & Ridwan, 2019) that another online learning media can also help students to be well motivated to learn. It means that podcasts application can give motivation to the students.…”
Section: 2mentioning
confidence: 99%
“…Numerous research studies have investigated the efficacy of integrating technology in education particularly the exploration of the most current social media in language learning some of them are, WhatsApp (Setyowati, 2019), (Priyambudi et al, 2021), (Azmi et al, 2016), (Wulandari et al, 2019), (Bensalem & Al-Zubaidi, 2018), (Hanim, 2021), (Dahdal, 2020), telegram (Xodabande, 2017), (Aghajani & Adloo, 2018), (A. Abu-Ayfah, 2019), (Alahmad, 2020), (Odinokaya et al, 2021) and Tiktok (Hanim, 2021), (Xiuwen & Razali, 2021), (Afidah et al, 2021), (Geology, 2021), (Anumanthan & Hashim, 2022), (Hu & Du, 2022), (Hidayati, 2022). Several suggestions have been put forth to educate this generation, and one of them involves leveraging Web 2.0 technologies.…”
Section: Introductionmentioning
confidence: 99%